ENHANCING BRAND EXPERIENCE ALONG WITH EMOTIONAL ATTACHMENT TOWARDS TRUST AND BRAND LOYALTY - Elia Ardyan; Heny Kurnianingsih; Ginanjar Rahmawan; Utomo Wibisono; Winata Winata (Jurnal Manajemen dan Kewirausahaan, 2016)
Research on Samsung’s smartphone consumers in Surakarta, have aimed to (1) Test the influence of brand experience on brand trust; (2) Test brand beliefs on brand loyalty; (3) Test on emotional attachment brand experience; (4) Test emotional attachment on brand trust; (5) Test brand experience on brand loyalty. The sample of this research was obtained from 100 respondents who have purchased a Samsung smartphone with the number of the purchase more than once. Methods of analysis used in this study are Structural Equation Modelling. The results of this research indicate that: (1) Brand experience influenced brand trust positively and significantly; (2) The trust against a brand loyalty affect brand positively and significantly; (3) Brand experience have positive and significant effect on emotional attachment; (4) Emotional attachment affects brand trust positively and significantly; (5) Brand trust have the influence of brand loyalty positively but not significant.